ADHD and SCT Symptomatology in Relation to College Students' Use of Self-Regulated Learning Strategies. Issue 14 (December 2019) - Shelton, Christopher R.; Addison, William E.; Hartung, Cynthia M.
Objective: The present study examined the relation between self-regulated learning (SRL) strategies and ADHD and sluggish cognitive tempo (SCT) symptomatology.Method: Participants were 303 college students, aged 18 to 25 ( M = 20.04, SD = 1.45), from a Midwestern university who completed the Barkley Adult ADHD Rating Scale-IV (BAARS-IV), and a shortened, generalized version of the Motivated Strategies for Learning Questionnaire (MSLQ).Results: Among college students, inattention symptomatology was consistently predictive of deficits in use of value, expectancy, and self-regulation strategies, while SCT symptomatology was only predictive of deficits in the use of self-regulation strategies.Conclusion: This study is the first to examine the relation between SCT symptomatology and SRL strategy use in college students. The findings revealed that SRL strategy use differs between college students exhibiting ADHD or SCT symptomatology. Remediation focusing on these deficits would likely increase academic achievement. Clinical implications, limitations, and suggestions for future research are discussed.